Hydrodynamic modelling of overtopping flow over granular dikes - F.N. Cantero-Chinchilla; R.J. Bergillos; O. Castro-Orgaz (Ingeniería del Agua)
This paper presents a comparative analysis of the last advances in depth-averaged modelling of overtopping flow over granular dikes. Among the most relevant models in this field, three families of models are described: (i) non-hydrostatic models with sediment transport, (ii) hydrostatic models with sediment transport and dynamic granular beds, and (iii) hydrostatic models with sediment transport as bed-load. To study their suitability, examples of the three families of models are compared using experimental data of dike overtopping. Whilst the hydrostatic model with bed-load sediment transport shows a fair agreement with the experimental data, the results by the non-hydrostatic model produces a more accurate free surface profile up to the dike crest domain. The results by the hydrostatic model assuming dynamic bed deformation enhances the predictions near the dike toe downstream. Finally, the limitations of the models are discussed.